Comparison of Variations Between Spectral Doppler and Gaussian Surface Integration Methods for Umbilical Vein Blood Volume Flow. (7th August 2020) - Rubin, Jonathan M.; Li, Sibo; Fowlkes, J. Brian; Sethuraman, Shriram; Kripfgans, Oliver D.; Shi, William; Treadwell, Marjorie C.; Jago, James R.; Leichner, Ronald D.; Pinter, Stephen Z.
Abstract : Objectives: We are studying a new method for estimating blood volume flow that uses 3‐dimensional ultrasound to measure the total integrated flux through an ultrasound‐generated Gaussian surface that intersects the umbilical cord. This method makes none of the assumptions typically required with standard 1‐dimensional spectral Doppler volume flow estimates. We compared the variations in volume flow estimates between techniques in the umbilical vein. Methods: The study was Institutional Review Board approved, and all 12 patients gave informed consent. Because we had no reference standard for the true umbilical vein volume flow, we compared the variations of the measurements for the flow measurement techniques. At least 3 separate spectral Doppler and 3 separate Gaussian surface measurements were made along the umbilical vein. Means, standard deviations, and coefficients of variation (standard deviation/mean) for the flow estimation techniques were calculated for each patient. P  < .05 was considered significant. Results: The ranges of the mean volume flow estimates were 174 to 577 mL/min for the spectral Doppler method and 100 to 341 mL/min for the Gaussian surface integration (GSI) method. The mean standard deviations (mean ± SD) were 161 ± 95 and 45 ± 48 mL/min for the spectral Doppler and GSI methods, respectively ( P  < .003). The mean coefficients of variation were 0.46 ± 0.17 and 0.18 ± 0.14 for the spectral Doppler and GSI methods respectively ( P  < 0.002). Conclusions: The new volume flow estimation method using 3‐dimensional ultrasound appears to have significantly less variation in estimates than the standard 1‐dimensional spectral Doppler method.